The Zelensky effect - Onuch, Olga 1982- (New perspectives on Eastern Europe and Eurasia, 2022)
With Russian shells raining on Kyiv and tanks closing in, American forces prepared to evacuate Ukraine’s leader. Just three years earlier, his apparent main qualification had been playing a president on TV. But Volodymyr Zelensky reportedly retorted, ‘I need ammunition, not a ride.’ Ukrainian forces won the battle for Kyiv, ensuring their country’s independence even as a longer war began for the southeast. You cannot understand the historic events of 2022 without understanding Zelensky. But the Zelensky effect is less about the man himself than about the civic nation he embodies: what makes Zelensky most extraordinary in war is his very ordinariness as a Ukrainian. The Zelensky Effect explains this paradox, exploring Ukraine’s national history to show how its now-iconic president reflects the hopes and frustrations of the country’s first ‘independence generation’. Interweaving social and political background with compelling episodes from Zelensky’s life and career, this is the story of Ukraine told through the journey of one man who has come to symbolise his country.